Gender Issues On Toefl ITP Score : A Case Study - Ukhrowi, Wim (EDUJ : English Education Journal, 2024)
The issue of gender is still debated by scientists. Some studies show that there is no difference between men and women in education. This research seeks to provide new nuances about gender issues in the TOEFL ITP test scores of prospective graduates of Unipdu in 2024. The data were obtained from 102 prospective graduates of Unipdu 2024, totaling 102 participants consisting of 52 male prospective graduates and 52 female prospective graduates who took the TOEFL ITP test. Data was obtained from the TOEFL ITP score. The statistical analysis used is using two independent sample t-tests on SPSS application. The average TOEFL score of males was higher than the average TOEFL score of females. The difference in average scores is: 389.0588 - 383.8431 = 5.2157, that is, the average TOEFL score of male prospective graduates is 5.2157 points higher than the average TOEFL score of female prospective graduates. The standard deviation of female graduate candidates is higher than the standard deviation of male graduate candidates. The difference is 26.59126 - 22.11553 = 4.47573. So it can be concluded that from the results of this study there is no significant difference between TOEFL ITP scores between males and females.